Benign intracranial hypotension caused by spontaneous cervical cerebrospinal fluid leak treated with cervical epidural blood patch: a case report - Acharya, Subhash Prasad; Parajuli, Bashu Dev; Aryal, Diptesh (Journal of Society of Anesthesiologists of Nepal, 2016)
Spontaneous cervical cerebrospinal fluid leak is a rare entity and occurs because of tear in cervical dural layer. Management has been conservative in the past but here we present this case that was managed successfully with cervical epidural blood patch. A 36-year-old man presented to neurology outpatient clinic with headache in occipito-frontal region and dizziness for 15 days and managed with various modalities without benefit. The severity of headache increased in standing and sitting position but relieved in supine position. There was no history of trauma, fever, photophobia, neck pain, tinnitus, weakness of other parts. Clinical examinations including neurological examinations were normal. So, magnetic resonance imaging of head and neck was obtained which showed dural leak in C3-C4 region. Adequate hydration, caffeine and oral medications were prescribed without benefit and then after 5 days, Anesthesiology department was consulted and was planned for cervical epidural blood patch. Under aseptic precaution in left lateral position with full neck flexion, 18g Tuohy needle was inserted in C5-C6 epidural space by loss of resistance technique to air, and 15 ml of the autologous blood was injected. Then patient was kept in supine position for 24 hours and neurological status was monitored frequently. Over the next two days, patient became asymptomatic and was discharged. The patient was regularly followed up weekly for six weeks and then monthly for six months and had no reoccurrence of symptoms or other findings.